Up-regulation of lncRNA WT1-AS ameliorates Aβ-stimulated neuronal injury through modulation of miR-186-5p/CCND2 axis in Alzheimer’s disease: Up-regulation of lncRNA WT1-AS in AD - Tang, Yun; Zhang, Xiaojiu; Wang, Shihui; Liu, Lu; Wang, Qing; Liu, Yufeng; Yu, Yadong; Zhai, Qijin (Cellular and Molecular Biology, 2024)
As a common neurodegenerative disorder, Alzheimer’s disease (AD) seriously threatens human life. Long non-coding RNAs (lncRNAs) exhibit essential functions in AD development. Nevertheless, the detailed effects and possible mechanisms of lncRNA Wilms tumor 1 Antisense RNA (WT1-AS) in AD are largely unknown. In our studies, a total of 30 serum samples from AD patients were collected, and WT1-AS expressions were detected through qRT-PCR analysis. Additionally, an in vitro AD model was constructed by treating Aβ1-42 in human neuroblastoma cells. Functional assays were implemented to assess the impacts of WT1-AS on Aβ1-42-stimulated human neuroblastoma cell proliferation together with apoptosis. Moreover, relationship of WT1-AS, microRNA (miR)-186-5p as well as cyclin D2 (CCND2) could be predicted through bioinformatics tools as well as proved via dual-luciferase reporter experiments. Our results showed that WT1-AS together with CCND2 were low-expressed, while miR-186-5p presented high expression in AD serum samples together with Aβ1-42-stimulated human neuroblastoma cells. WT1-AS over-expression or miR-186-5p depletion notably promoted the proliferation, reduced the apoptosis, and decreased the p-Tau protein expressions of human neuroblastoma cells induced with Aβ1-42. Moreover, miR-186-5p combined with WT1-AS, and CCND2 was modulated by miR-186-5p. Furthermore, CCND2 elevation partially offsets the impacts of miR-186-5p elevation on Aβ1-42-stimulated cell proliferation as well as apoptosis mediated with WT1-AS up-regulation. Our results indicated that up-regulation of lncRNA WT1-AS ameliorated Aβ-stimulated neuronal damage through modulating miR-186-5p/CCND2 axis, offering a novel direction for AD therapy.